Hydrolyzed protein formula improves the nutritional tolerance by increasing intestinal development and altering cecal microbiota in low-birth-weight piglets - Bai, Miaomiao; Liu, Hongnan; Yan, Yalu; Duan, Sufang; Szeto, Ignatius Man-Yau; He, Jian; Hu, Jinjie; Fu, Yawei; Xu, Kang; Xiong, Xia (Frontiers in Nutrition, 2024)
Background: Prematurity or low birth weight (LBW), poses a significant challenge in global health. Exploring appropriate and effective nutritional interventions is crucial for the growth and development of LBW infants. Hydrolyzed protein formula has been suggested as a potential solution to prevent intestinal dysfunction and improve digestion and absorption in infants.Objectives: This study aimed to investigate the benefits of hydrolyzed protein formula on feeding intolerance, intestinal morphological development, and microbiota in a LBW piglet model. Methods: A total of 24 male piglets (3 d of age, 0.95 -1.25 kg average BW) were assigned (8 pens/diet; 1 pigs/pen) into three dietary treatments and fed with a basic formula (BF), standard premature infant formula (SF) and hydrolyzed protein formula (HF) respectively, for 7 d. After the piglets sacrifice, growth performance, amino acid metabolism and intestinal morphology were assessed. 16S rRNA sequencing and microbial metabolic phenotypes analyzed the effects of different formula treatments on intestinal flora structure of LBW piglets.The HF diet reduced the rates of diarrhea and milk vomiting were reduced by 20.44% (P > 0.05) and 58.44% (P > 0.05), and decreased the crypt depth in the ileum while increasing the ratio of villus height/crypt depth and the mRNA expressions of y+ LAT1 and b0,+ AT in the ileum (P < 0.05). HF increased the final body weight, serum Thr and essential amino acid contents, and CAT2 and b0,+ AT mRNA expressions in ileal mucosa compared with the SF diet (P < 0.05). Microbiota sequencing results showed that the colonic microbial richness indices (Chao1, ACE, and observed species), the diversity indices (Shannon and Simpson), and the phyla Actinobacteriota, unidentified_Bacteria, Acidobacteriota and Actinobacteria, the genus Rubrobacter and RB41 were reduced (P < 0.05) in SF and HF groups. Microbial metabolic phenotypes analysis showed a reduction in the richness of biofilm-forming bacteria (P < 0.05). Conclusions: In summary, hydrolyzed protein formula had better nutrition and tolerance in LBW suckling piglets by improving amino acid transport and intestinal development, and regulating gut microbial communities.